Respuestas
Respuesta dada por:
1
Saludos
4x + 3y = 2 (1)
5x - 2y = -1 (2)
Multiplicamos por 2 (1) y por 3(2), queda
8x + 6y = 4 (1)
15x - 6y = -3 (2) se suman
-----------------------
23x = 1
(3)
Reemplazamos (3) en
4x + 3y = 2 (1)
![4 \frac{1}{23} +3y=2 4 \frac{1}{23} +3y=2](https://tex.z-dn.net/?f=4+%5Cfrac%7B1%7D%7B23%7D+%2B3y%3D2)
![3y=2- \frac{4}{23} 3y=2- \frac{4}{23}](https://tex.z-dn.net/?f=3y%3D2-+%5Cfrac%7B4%7D%7B23%7D)
![y= \frac{\frac{46}{23} - \frac{4}{23}}{3} y= \frac{\frac{46}{23} - \frac{4}{23}}{3}](https://tex.z-dn.net/?f=y%3D++%5Cfrac%7B%5Cfrac%7B46%7D%7B23%7D+-+%5Cfrac%7B4%7D%7B23%7D%7D%7B3%7D+)
![y= \frac{\frac{42}{23} }{3} = \frac{42}{69} = \frac{14}{23} y= \frac{\frac{42}{23} }{3} = \frac{42}{69} = \frac{14}{23}](https://tex.z-dn.net/?f=y%3D++%5Cfrac%7B%5Cfrac%7B42%7D%7B23%7D+%7D%7B3%7D+%3D+%5Cfrac%7B42%7D%7B69%7D+%3D+%5Cfrac%7B14%7D%7B23%7D+)
(4) respuesta
(5) respuesta
Para comprobar reemplazamos (4)(5) en (1)
4x + 3y = 2 (1)
![4 \frac{1}{23} +3 \frac{14}{23} =2 4 \frac{1}{23} +3 \frac{14}{23} =2](https://tex.z-dn.net/?f=4+%5Cfrac%7B1%7D%7B23%7D+%2B3+%5Cfrac%7B14%7D%7B23%7D+%3D2)
![\frac{4}{23} + \frac{42}{23} =2 \frac{4}{23} + \frac{42}{23} =2](https://tex.z-dn.net/?f=+%5Cfrac%7B4%7D%7B23%7D+%2B+%5Cfrac%7B42%7D%7B23%7D+%3D2)
![\frac{46}{23} =2 \frac{46}{23} =2](https://tex.z-dn.net/?f=+%5Cfrac%7B46%7D%7B23%7D+%3D2)
2=2
Espero te sirva
4x + 3y = 2 (1)
5x - 2y = -1 (2)
Multiplicamos por 2 (1) y por 3(2), queda
8x + 6y = 4 (1)
15x - 6y = -3 (2) se suman
-----------------------
23x = 1
Reemplazamos (3) en
4x + 3y = 2 (1)
Para comprobar reemplazamos (4)(5) en (1)
4x + 3y = 2 (1)
2=2
Espero te sirva
Preguntas similares
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años